Inherited bone marrow failure syndromes: phenotype as a tool for early diagnostic suspicion at a major reference center in Mexico - Leal-Anaya, Paula; Kimball, Tamara N.; Yanez-Felix, Ana Lucia; Fiesco-Roa, Moisés Ó.; García-de Teresa, Benilde; Monsiváis, Angélica; Juárez-Velázquez, Rocío; Lieberman, Esther; Villarroel, Camilo; Yokoyama, Emiy; Fernández-Hernández, Liliana; Rivera-Osorio, Anet; et al. (Frontiers in Genetics, 2024)
INTRODUCTION. The inherited bone marrow failure syndromes (IBMFS) are a group of rare disorders characterized by bone marrow failure (BMF), physical abnormalities, and an increased risk of neoplasia. The National Institute of Pediatrics (INP) is a major medical institution in Mexico where patients with BMF receive a complete approach that includes paraclinical tests. Readily recognizable features, like the hematological, and distinctive physical phenotypes, identified by clinical dysmorphologists, remain crucial for the diagnosis and management of these patients, particularly in circumstances where next generation sequencing (NGS) is not easily available. Here we describe a group of Mexican patients with a high clinical suspicion of an IBMFS. METHODS. We performed a systematic retrospective analysis of the medical records of patients who had a high IBMFS suspicion at our institution from January 2018 to July 2021. An initial assessment included first ruling out acquired causes of BMF by the Hematology Department, and referral of the patient to the department of Human Genetics for physical examination to search for specific phenotypes suggesting an IBMFS. Patients with high suspicion of having an IBMFS were classified into two main groups: 1) specific IBMFS, including dyskeratosis congenita (DC), Diamond-Blackfan anemia (DBA), Shwachman-Diamond syndrome (SDS), thrombocytopenia with absent radii (TAR), and severe congenital neutropenia (SCN); and 2) undefined IBMFS (UI). RESULTS. We established a high suspicion of having an IBMFS in 48 patients. At initial evaluation, the most common hematologic features were bicytopenia (20%) and aplastic anemia (16%); three patients received hematopoietic stem cell transplantation. Among patients with a suspicion of an IBMFS, the most common physical abnormality was